Increased pulmonary artery diameter is associated with reduced FEV1 in former World Trade Center workers. (19th August 2019) - de la Hoz, Rafael E.; Jeon, Yunho; Reeves, Anthony P.; San José Estépar, Raúl; Liu, Xiaoyu; Doucette, John T.; Celedón, Juan C.; Nolan, Anna
Abstract: Rationale: Occupational exposures at the WTC site after September 11, 2001 have been associated with several presumably inflammatory lower airway diseases. Pulmonary arterial enlargement, as suggested by an increased ratio of the diameter of the pulmonary artery to the diameter of the aorta (PAAr) has been reported as a computed tomographic (CT) scan marker of adverse respiratory health outcomes, including WTC‐related disease. In this study, we sought to utilize a novel quantitative CT (QCT) measurement of PAAr to test the hypothesis that an increased ratio is associated with FEV1 below each subject's statistically determined lower limit of normal (FEV1  < LLN). Methods: In a group of 1, 180 WTC workers and volunteers, we examined whether FEV1  < LLN was associated with an increased QCT‐measured PAAr, adjusting for previously identified important covariates. Results: Unadjusted analyses showed a statistically significant association of FEV1  < LLN with PAAr (35.3% vs 24.7%, P  = 0.0001), as well as with height, body mass index, early arrival at the WTC disaster site, shorter WTC exposure duration, post‐traumatic stress disorder checklist (PCL) score, wall area percent and evidence of bronchodilator response. The multivariate logistic regression model confirmed the association of FEV1  < LLN with PAAr (OR 1.63, 95% CI 1.21, 2.20, P  = 0.0015) and all the unadjusted associations, except for PCL score. Conclusions: In WTC workers, FEV1  < LLN is associated with elevated PAAr which, although likely multifactorial, may be related to distal vasculopathy, as has been hypothesized for chronic obstructive pulmonary disease.